OPTN/SRTR 2015 Annual Data Report: Heart. (January 2017) - Colvin, M.; Smith, J. M.; Skeans, M. A.; Edwards, L. B.; Uccellini, K.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
Abstract: The number of heart transplant candidates and transplants performed continued to rise each year. In 2015, 2819 heart transplants were performed. In addition, the number of new adult candidates on the waiting list increased 51% since 2004. The number of adult heart transplant survivors continued to increase, and in 2015, 29, 172 recipients were living with heart transplants. Patient mortality following transplant has declined. The number of pediatric candidates and transplants performed also increased. New listings for pediatric heart transplants increased from 451 in 2004 to 644 in 2015. The number of pediatric heart transplants performed each year increased from 297 in 2004 to 460 in 2015. Among pediatric patients who underwent transplant in 2014, death occurred in 7.2% at 6 months and 9.6% at 1 year.